2020
DOI: 10.1186/s11671-020-3250-1
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum disulfide quantum dots: preparation, structure, and properties

Abstract: Tantalum disulfide (TaS 2) two-dimensional film material has attracted wide attention due to its unique optical and electrical properties. In this work, we report the preparation of 1 T-TaS 2 quantum dots (1 T-TaS 2 QDs) by top-down method. Herein, we prepared the TaS 2 QDs having a monodisperse grain size of around 3 nm by an effective ultrasonic liquid phase exfoliation method. Optical studies using UV-Vis, PL, and PLE techniques on the as-prepared TaS 2 QDs exhibited ultraviolet absorption at 283 nm. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…[ 111 ] It exhibits an increase in bandgap from indirect to direct due to confinement effect in the electronic structure. [ 112 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 111 ] It exhibits an increase in bandgap from indirect to direct due to confinement effect in the electronic structure. [ 112 ]…”
Section: Methodsmentioning
confidence: 99%
“…[111] It exhibits an increase in bandgap from indirect to direct due to confinement effect in the electronic structure. [112] Figure 11 shows a collection of OM images of few-layer 1 T-TaS 2 flakes of different thicknesses deposited onto 90 nm SiO 2 /Si substrate. The bottom panel of Figure 11 shows the color charts correlating the thickness of 1T-TaS 2 flakes with their apparent color.…”
Section: Tasmentioning
confidence: 99%
“…Several methods have been demonstrated to produce layered TaS 2, such as chemical vapor deposition (CVD) 27 , mechanical cleavages 21 , intercalation 28 , ultrasonication [29][30][31] , or liquid-phase exfoliation 22 . However, the CVD method remains to be improved before it can be used to produce large-domain homogeneous TaS 2 films.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and functions of TaS 2 have been widely examined as an example of a 2D metallic RMC. [ 212 ] Peng et al. found the effectiveness of TaS 2 monolayer on superconductivity, carrier density, and domain shape.…”
Section: The Properties Of Rmcsmentioning
confidence: 99%
“…[211] The structure and functions of TaS 2 have been widely examined as an example of a 2D metallic RMC. [212] Peng et al found the effectiveness of TaS 2 monolayer on superconductivity, carrier density, and domain shape. [213] Also, the bandgap of TaS 2 quantum dots increased with respect to NSs and was found to be 3.69 eV.…”
Section: Electrical and Optical Properties Of Rmcsmentioning
confidence: 99%